TRAJETÓRIA DA PSICOLOGIA DA EDUCAÇÃO NO CURSO DE PEDAGOGIA DA UEPG (1962-2012): CONFORMAÇÃO E CONSOLIDAÇÃO DO CAMPO DE CONHECIMENTO - Souza, Audrey Pietrobelli de (2016)
The general objective of this thesis is to analyze the trajectory of the Education Psychology area in the Education Course at the State University of Ponta Grossa – UEPG from 1962 to 2012. This period was chosen because the course was implemented in the institution in 1962 and in 2012 the most recent course curricular reform process occurred. More specifically, this research aims at comprehending the conditions that favored changes promoted in the Education Psychology area in the Education Course at UEPG. The study also intends to identify the main theoretical matrices that made up the course curricular structure along the years and explain how the process of insertion and appropriation of the interactionist perspective occurred in the subjects offered. Such perspective refers mainly to the Jean Piaget’s Genetic Epistemology and Lev S. Vigotski’s Cultural- Historical Theory taking into consideration their interfaces with the national scenery of the Education and Education Psychology fields. This investigation was based on the theoretical background of History of School Subjects, discussions put forward by Roger Chartier on the concept of appropriation and the category of field systematized by Pierre Bourdieu. It also gathers a set of written and oral sources to make up the documental corpus. The printed documents are Books of Activity Reports that belong to the Philosophy, Sciences and Language College of Ponta Grossa, UEPG University Brochures, Course Curricular Restructuring Processes and Programs of Academic Subjects which are comprised in the area Class Diaries. The oral sources used are semi-structured interviews, carried out with eleven professors who work and∕or used to work teaching in the Education Psychology area at the institution being investigated. The mediation between the conceptual apparatus and documental data allows this study to defend the thesis that not only did the constitution process of Education Psychology in the Education course at UEPG follow the movement and history of this area of knowledge in the national educational scenery, but was also influenced by the interests, forces and struggles that marked the curricular reform process to which the course was submitted. Also, the history of this area was seen to be intertwined with elements of its professor’s trajectories in the field of Education Psychology, in the teacher education speciality, in Education and in the teaching practice. This leads to the conclusion that the trajectory of Education Psychology in the Education Course at UEPG was marked by three significant periods: the first, between 1962 and 1972 corresponds to the introduction of Education Psychology in the Education Course and highlights the philosophical focus that characterized the area throughout this decade; the second, between 1973 and 1990, reveals a substantial change inside the Education Psychology field, which gains a more psychological approach with a curricular organization marked by technical principles; the third, between 1991 and 2012 emphasizes a cognitivist-cultural focus that began to characterize the Education Psychology area in the Education Course at UEPG. Among its conclusions, the study highlights specially the issue posed to any and all research on the history of certain area or academic subject that is to understand it as the result of a social and historical construction process.